2023
DOI: 10.3389/fpls.2023.1154208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis identifies candidate genes related to seed coat color in rapeseed

Abstract: Yellow seed coat in rapeseed (Brassica napus) is a desirable trait that can be targeted to improve the quality of this oilseed crop. To better understand the inheritance mechanism of the yellow-seeded trait, we performed transcriptome profiling of developing seeds in yellow- and black-seeded rapeseed with different backgrounds. The differentially expressed genes (DEGs) during seed development showed significant characteristics, these genes were mainly enriched for the Gene Ontology (GO) terms carbohydrate meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
1
1
0
Order By: Relevance
“…Comparative studies between peanut varieties with different seed sizes and oil levels identified genes and networks involved in fatty acid synthesis, suggesting strategies for improving seed yield and quality (Yang et al, 2023). Similar to research conducted on peanuts, studies in other crops like safflower, soybean, and rapeseed have also explored key genes and networks involved in regulating traits such as like seed size, oil content, and fatty acid composition (Fan et al, 2023;Guan et al, 2023;Zhao et al, 2023). Research on oleic acid content between cultivars highlighted the role of FAB2 in unsaturated fatty acid biosynthesis and lipid oxidation (Liu et al, 2018), which agreed with the reports in other plants (Dar et al, 2017;He et al, 2020).…”
Section: The Trait-related Regulation Of Peanut Seed Development Base...supporting
confidence: 53%
“…Comparative studies between peanut varieties with different seed sizes and oil levels identified genes and networks involved in fatty acid synthesis, suggesting strategies for improving seed yield and quality (Yang et al, 2023). Similar to research conducted on peanuts, studies in other crops like safflower, soybean, and rapeseed have also explored key genes and networks involved in regulating traits such as like seed size, oil content, and fatty acid composition (Fan et al, 2023;Guan et al, 2023;Zhao et al, 2023). Research on oleic acid content between cultivars highlighted the role of FAB2 in unsaturated fatty acid biosynthesis and lipid oxidation (Liu et al, 2018), which agreed with the reports in other plants (Dar et al, 2017;He et al, 2020).…”
Section: The Trait-related Regulation Of Peanut Seed Development Base...supporting
confidence: 53%
“…In terms of the MF category, major polymorphic SNPs were linked to GO terms such as binding (GO:0005488), organic cyclic compound binding (GO:0097159), heterocyclic compound binding (GO:1901363), ion binding (GO:0043167), and protein binding (GO:0005515). Guan et al (2023) previously reported that the GO enrichment analysis of highly expressed genes during seed development in B. napus highlighted the importance of gene expression, translational initiation, and cellular nitrogen compound metabolic processes in the BP category; intracellular anatomical structures, organelles, and intracellular organelles in the CC category; and translation regulator activity, translation factor activity, RNA binding, and nucleic acid binding in the MF category [ 27 ]. These findings align with our results, thus confirming the significance of these terms in seed development in rapeseed.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the MF category, the major polymorphic SNPs were linked to GO terms such as binding (GO:0005488), organic cyclic compound binding (GO:0097159), heterocyclic compound binding (GO:1901363), ion binding (GO:0043167), and protein binding (GO:0005515). Guan et al (2023) reported that GO enrichment analysis of genes with high expression levels during seed development showed in B. napus that the top three terms were gene expression, translational initiation, and cellular nitrogen compound metabolic process in the BP category; intracellular anatomical structure, organelle, and intracellular organelle in the CC category; and translation regulator activity, translation factor activity, RNA binding, and translation regulator activity, nucleic acid binding in the MF category [35]. These results suggest that the top three GO terms may play an important role in seed development in B. napus, and our results confirmed all of these terms (Table S5).…”
Section: Discussionmentioning
confidence: 99%